Compound heterozygous CACNA1H mutations associated with severe congenital amyotrophy. Issue 1 (1st January 2019) - Carter, Melissa T.; McMillan, Hugh J.; Tomin, Andriy; Weiss, Norbert
ABSTRACT: Neuromuscular disorders encompass a wide range of conditions often associated with a genetic component. In the present study, we report a patient with severe infantile-onset amyotrophy in whom two compound heterozygous variants in the gene CACNA1H encoding for Cav 3.2 T-type calcium channels were identified. Functional analysis of Cav 3.2 variants revealed several alterations of the gating properties of the channel that were in general consistent with a loss-of-channel function. Taken together, these findings suggest that severe congenital amyoplasia may be related to CACNA1H and would represent a new phenotype associated with mutations in this gene.